Evaluasi Karakter Agronomi Enam Genotipe Semangka Hibrida (F1) Hasil Seleksi Galur Murni - Alex Kurnia Putra; Anung Wahyudi; Ria Putri (Politeknik Negeri Lampung., 2025)
National watermelon production in the last three years has decreased. The need for superior seeds to increase national fruit production. Plant breeding programs can assemble superior hybrid seeds to increase national fruit production. This study aims to determine the agronomic characters of the tested genotypes and obtain superior genotypes from the tested genotypes. The materials used were six genotypes of F1 hybrid watermelons as a result of pure line selection and four F1 hybrid varieties as control varieties. This study used A Randomized Block Design (RBD) with one factor, namely the F1 hybrid watermelon genotype, repeated twice, resulting in 20 experimental units. The results of the F-test analysis on quantitative variables have a significant effect, followed by the Duncan Multiple Range Test (DMRT) levels of 5%. Qualitative variables were analyzed using dendrogram analysis. The results of this study showed the diversity of agronomic characters from all the genotypes tested. The dominant genotype WM 2210-0616 has superior quantitative characteristics compared to the control varieties because it has large cotyledons, early female flowering, heaviest fruit, large fruit size, thick skin and flesh, high level of sweetness, percentage of fruiting plants and high fruit weight per hectare. Dendogram analysis on the qualitative variables there are two clusters with a similarity level of 72%. The results of this study can be used as material for making descriptions of varieties for registration of new superior varieties.